Dual RNA 3’-end processing of H2A.X messenger RNA maintains DNA damage repair throughout the cell cycle - Griesbach, E; Schlackow, M; Marzluff, WF; Proudfoot, NJ (Springer Nature, 2021)
Phosphorylated H2A.X is a critical chromatin marker of DNA damage repair (DDR) in higher eukaryotes. However, H2A.X gene expression remains relatively uncharacterised. Replication-dependent (RD) histone genes generate poly(A)- mRNA encoding new histones to package DNA during replication. In contrast, replication-independent (RI) histone genes synthesise poly(A)+ mRNA throughout the cell cycle, translated into histone variants that confer specific epigenetic patterns on chromatin. Remarkably H2AFX, encoding H2A.X, is a hybrid histone gene, generating both poly(A)+ and poly(A)- mRNA isoforms. Here we report that the selective removal of either mRNA isoform reveals different effects in different cell types. In some cells, RD H2A.X poly(A)- mRNA generates sufficient histone for deposition onto DDR associated chromatin. In contrast, cells making predominantly poly(A)+ mRNA require this isoform for de novo H2A.X synthesis, required for efficient DDR. This highlights the importance of differential H2A.X mRNA 3’-end processing in the maintenance of effective DDR.